2012
DOI: 10.1371/journal.ppat.1003056
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Architecture and Biogenesis of Membrane Structures Associated with Hepatitis C Virus Replication

Abstract: All positive strand RNA viruses are known to replicate their genomes in close association with intracellular membranes. In case of the hepatitis C virus (HCV), a member of the family Flaviviridae, infected cells contain accumulations of vesicles forming a membranous web (MW) that is thought to be the site of viral RNA replication. However, little is known about the biogenesis and three-dimensional structure of the MW. In this study we used a combination of immunofluorescence- and electron microscopy (EM)-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
669
2
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 468 publications
(731 citation statements)
references
References 70 publications
37
669
2
6
Order By: Relevance
“…Of note, the timescale of this process as observed in this study (up to 10 min from formation of the NS5A-DFCP1 puncta to their eventual dissociation -see Figs 6 and 7), is consistent with the timescale observed previously for the transient association of GFP-DFCP1 and RFP-LC3 during autophagosome formation (also approximately 10 min) (Axe et al, 2008). The difference in size between autophagosomes (v1.5 mm) and DMVs (100-150 nm) (Romero-Brey et al, 2012) is also consistent with the hypothesis that DMVs derive from autophagosomes.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Of note, the timescale of this process as observed in this study (up to 10 min from formation of the NS5A-DFCP1 puncta to their eventual dissociation -see Figs 6 and 7), is consistent with the timescale observed previously for the transient association of GFP-DFCP1 and RFP-LC3 during autophagosome formation (also approximately 10 min) (Axe et al, 2008). The difference in size between autophagosomes (v1.5 mm) and DMVs (100-150 nm) (Romero-Brey et al, 2012) is also consistent with the hypothesis that DMVs derive from autophagosomes.…”
Section: Discussionsupporting
confidence: 90%
“…Our data complement the recent, elegant study of Romero-Brey et al (2012), who showed that the membranous web in HCV-infected cells comprised predominantly DMVs and derived from the ER. In particular, they identified DMVs as protrusions from the ER membrane.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations